An Eight-year Retrospective Study in “Flipped” Pharmacokinetics Courses - Persky, Adam M. (Am J Pharm Educ, 2014)
Objective. To assess the impact on student performance of increased active learning strategies in a foundational pharmacokinetics course and a clinical pharmacokinetics course over an 8-year period. Design. A foundational pharmacokinetics course with a lecture-with-active-learning (LAL) format was redesigned to a recitation-format (REC) using smaller groups of students (ie, the class divided into thirds) and eventually to a team-based learning (TBL) format. The lecture-based clinical pharmacokinetics course was redesigned to a case-based learning (CBL) format to encourage preclass preparation with class time used for application; this course format underwent minor redesigns over an 8-year period. An analysis of covariance (ANCOVA) was performed on examination scores in the clinical course based on foundational course format changes. End-of-semester student evaluations of the course were used as a secondary measure of impact. Assessment. The highest grades in the clinical course were associated with the TBL format within the foundational course compared to LAL format (effect size 0.78). The REC format in the foundational course compared to LAL was associated with higher performance in the clinical course (effect size 0.50). Examination performance in the clinical course had a small increase when the foundational course was transitioned from the REC format to the TBL format (effect size 0.27). There was a trend within the foundational course that overall student ratings of the course decreased with enhanced self-directed learning; there was no change in overall ratings of the clinical course. Conclusion. Increasing the amount of active learning within the foundational pharmacokinetics course increases performance in the clinical course but this increase in performance may be associated with decreases in student evaluations of the foundational course.